The impact of mood on empathy for pain: Evidence from an EEG study. (27th April 2017) - Li, Xiang; Meng, Xianxin; Li, Hong; Yang, Jiemin; Yuan, Jiajin
Abstract: The current work investigated whether the neural correlates of empathy for pain are altered by mood valence of observers. Following mood induction, participants watched pictures representing painful or nonpainful situations. We used EEG to record neural activity and assessed event‐related desynchronization at central sites during pain observation. Greater mu desynchronization was observed during painful relative to nonpainful situations in positive and neutral mood but not in negative mood. We also found that the pain empathy effect, indexed by mu suppression differences between painful and nonpainful conditions, was smaller in negative than in neutral and positive mood, while this effect was similar between neutral and positive mood. The current study demonstrates that observers' mood states influence the motoric component of empathy for pain, and specifically the negative mood suppresses the motoric empathic resonance for others' pain.